Citizens' preferences for the conservation of agricultural genetic resources - Pouta, Eija; Tienhaara, Annika; Ahtiainen, Heini (Frontiers in Genetics, 2014)
Evaluation of conservation policies for agricultural genetic resources (AgGR) requires information on the use and non-use values of plant varieties and animal breeds, as well as on the preferences for in situ and ex situ conservation. We conducted a choice experiment to estimate citizens’ willingness to pay for AgGR conservation programmes in Finland, and used a latent class model to identify heterogeneity in preferences among respondent groups. The findings indicate that citizens have a high interest in the conservation of native breeds and varieties, but also reveal the presence of preference heterogeneity. Five respondent groups could be identified based on latent class modelling: one implying lexicographic preferences, two with reasoned choices, one indicating uncertain support and one with a preference for the current status of conservation. The results emphasise the importance of in situ conservation of native cattle breeds and plant varieties in developing conservation policies.